Can Religious Tourism Meet Tourist Satisfaction through its Halal-Friendly? - Saifudin, Saifudin (Universitas Islam Negeri Sunan Kudus, 2021)
This study aims to determine the effect of halal-friendly tourism on tourist satisfaction in Demak religious tourism. The exogenous variables of halal-friendly accommodations, halal foods, halal-friendly facilities, halal-friendly services, and halal-friendly locals and other travellers were tested for their effect on the endogenous variable, namely tourist satisfaction. Sampling using purposive sampling. The data used are primary data obtained from 534 respondents. The study results explain that halal-friendly accommodations, halal-friendly facilities, and halal-friendly locals and other travellers affect tourist satisfaction. However, halal foods and halal-friendly services do not affect tourist satisfaction.